2016
DOI: 10.1093/pm/pnw245
|View full text |Cite
|
Sign up to set email alerts
|

Durations of Opioid, Nonopioid Drug, and Behavioral Clinical Trials for Chronic Pain: Adequate or Inadequate?

Abstract: No common nonopioid treatment for chronic pain has been studied in aggregate over longer intervals of active treatment than opioids. To dismiss trials as "inadequate" if their observation period is a year or less is inconsistent with current regulatory standards. The literature on major drug and nondrug treatments for chronic pain reveals similarly shaped distributions across modalities. Considering only duration of active treatment in efficacy or effectiveness trials, published evidence is no stronger for any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Cochrane reviews have shown the combination of 200 mg ibuprofen/500 mg acetaminophen is one of the strongest pain reliever combinations available, more effective than low-dose opioids alone for chronic pain conditions such as back pain [13,14]. Other studies indicate no major difference between opioid and non-opioid approaches [15]. In terms of OD risk, however, the safety profile is stronger for non-opioids and atypical opioid agents, the latter including tapentadol and buprenorphine (Belbuca or Butrans).…”
Section: Different Strategies For Different Types Of Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochrane reviews have shown the combination of 200 mg ibuprofen/500 mg acetaminophen is one of the strongest pain reliever combinations available, more effective than low-dose opioids alone for chronic pain conditions such as back pain [13,14]. Other studies indicate no major difference between opioid and non-opioid approaches [15]. In terms of OD risk, however, the safety profile is stronger for non-opioids and atypical opioid agents, the latter including tapentadol and buprenorphine (Belbuca or Butrans).…”
Section: Different Strategies For Different Types Of Painmentioning
confidence: 99%
“…Non-opioid pharmacology and behavioral interventions, if considered with the same criteria, show no greater efficacy than opioids. It also suggests that the significant morbidity and mortality from non-opioid pain relievers has not been considered fully [15]. This in no way lessens the urgency of safer prescribing but does reflect the lack of scientific rigor of some of the recommendations.…”
Section: Kumar Sidebar Continuedmentioning
confidence: 99%
“…Included are opioid and non-opioid pharmacotherapies, physical therapy, psychological and behavioral therapies, complementary and alternative medicine strategies, peripheral procedures, spinal procedures, and surgery ( Table 1 ). As with opioid clinical trials, controlled trials of non-opioid analgesic strategies are typically short (< 12 weeks) and so long-term effectiveness data for chronic pain using these strategies is limited ( Tayeb et al, 2016 ).…”
Section: Effective Pain Management Strategies: Beyond Prescriptionmentioning
confidence: 99%
“…It is worth noting that the 2016 CDC guidelines themselves have been criticized for inappropriately categorizing their recommendations as grade A, which is defined as the highest standard of evidence and usually requires RCT data. According to some critics, the CDC guidelines were based on case studies and expert opinion, which does not typically qualify for grade A ratings (American Medical Association, 2016;Mundkur, Gordon, & Kertesz, 2017;Tayeb, Barreiro, Bradshaw, Chui, & Carr, 2016).…”
Section: Misperception 4: More People Die From Prescription Od Deathsmentioning
confidence: 99%